WPŁYW UMUZYKALNIENIA NA PRZYSWAJANIE PODSYSTEMU FONICZNEGO U UCZĄCYCH SIĘ JĘZYKÓW OBCYCH: WYNIKI BADANIA - Piegzik, Wioletta (Neofilolog, 2019)
This report presents the results of a study into the relationship between musical ability and the development of a phonological system by foreign language learners. Our own experiences both as a foreign language teacher and as a musical group leader have raised a number of questions and lines of enquiry. These challenge previous researchers’ findings concerning the allegedly absolutely positive effect of music on language learning and as a result this study has been undertaken. After a brief theoretical presentation, we describe the research project in which learners abilities to distinguish and produce different phonemes as well as the prosody of the language studying are analyzed. Two groups of learners were compared in this study. One group attended a music school. The second group had no musical experience. The study showed that receptive skills were not significantly different between the two groups. The group of learners with musical training was more articulate but this was the only difference. The statistical approach used in analysis of data was the Wilcoxon test.